2017
DOI: 10.4314/rj.v4i1.6f
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices of dental professionals in Rwanda towards the benefits and applications of teledentistry

Abstract: Background: Currently, the use of teledentistry is still low in developing countries. In Rwanda, the state of teledentistry is undocumented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
3
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 10 publications
8
29
3
7
Order By: Relevance
“…The questionnaire was derived from previous literature, with modifications. [ 22 23 , 26 27 , 29 ] A pilot test with 10 participants validated the questionnaire for logical flow, organization, language, syntax, and content. The questionnaire has good reliability as Cronbach α ranged between 0.67 and 0.82.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire was derived from previous literature, with modifications. [ 22 23 , 26 27 , 29 ] A pilot test with 10 participants validated the questionnaire for logical flow, organization, language, syntax, and content. The questionnaire has good reliability as Cronbach α ranged between 0.67 and 0.82.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The comparison of results in the literature indicated that the knowledge about teledentistry differs by country, level of education, and years of experience. [ 22 23 24 25 26 ] For example, 74.4%–88.6% of dentists in India and Rwanda were aware of teledentistry,[ 22 23 24 25 ] as compared to 37.4% in Pakistan. [ 25 ] Dental students were found to be less knowledgeable and enthusiastic about teledentistry than dental faculty or practicing dentists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies conducted by Cooper and Engeswick, Purohit et al , Tomar et al , Murererehe et al , and Latif et al also revealed similar demographic details, but lesser values were found by Ata and Ozkan. [ 12 13 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another branch of telemedicine is tele-dentistry, which refers to use of ICTS in the field of dentistry (Bhargava et al, 2020). However, telemedicine services are offered more predominantly in developed countries than in developing countries (Murererehe et al, 2017).…”
Section: Use Of Icts In the Field Of Healthcarementioning
confidence: 99%